1986
DOI: 10.1128/jcm.24.1.52-55.1986
|View full text |Cite
|
Sign up to set email alerts
|

Associated mortality and clinical characteristics of nosocomial Pseudomonas maltophilia in a university hospital

Abstract: We studied the spectrum of clinical disease in 99 patients with nosocomial Pseudomonas maltophilia isolates at the University of Virginia Hospital from 1981 through 1984. The annual rate of isolation increased from 7.1 to 14.1 per 10,000 patient discharges. A crude mortality rate of 43% was docuniented in all patients from whom the organism was cultured, and the data include 12 patients with nosocomial bacteremia (four deaths). Risk factors associated with death for patients having a P. maltophilia isolate inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
35
0
4

Year Published

1987
1987
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(42 citation statements)
references
References 37 publications
(35 reference statements)
3
35
0
4
Order By: Relevance
“…1,4,8,[20][21][22][23] However, immunosuppressed or medically ill patients were a significant percentage of patients in these studies, possibly leading to the higher mortality rate. 1,4,20,22,23 In the only other report, to our knowledge, focusing on S. maltophilia VAP in the critically ill trauma patient population, a 23.1% all-cause mortality rate was observed in 26 patients. 8 This differed from the 13% all-cause mortality rate and the 7% VAP-related mortality rate in our study.…”
Section: Discussionmentioning
confidence: 91%
“…1,4,8,[20][21][22][23] However, immunosuppressed or medically ill patients were a significant percentage of patients in these studies, possibly leading to the higher mortality rate. 1,4,20,22,23 In the only other report, to our knowledge, focusing on S. maltophilia VAP in the critically ill trauma patient population, a 23.1% all-cause mortality rate was observed in 26 patients. 8 This differed from the 13% all-cause mortality rate and the 7% VAP-related mortality rate in our study.…”
Section: Discussionmentioning
confidence: 91%
“…Stenotrophomonas are associated with various ecosystems and clinical conditions (Berg et al ., ) and is one of the most commonly isolated species from nosocomial infections (Morrison et al ., ; Senol, ; Wakino et al ., ) and respiratory samples of patients with CF (Ballestero et al ., ; Denton, ; Goss et al ., ; Marzuillo et al ., ). The species within the genus Stenotrophomonas exhibit only limited phenotypic characteristics, and the 16S rRNA gene sequence similarity is high.…”
Section: Resultsmentioning
confidence: 99%
“…Since it is able to grow in many different media in the presence of most antimicrobial agents, S. maltophilia is isolated with increasing frequency as a nosocomial pathogen. The annual isolation rate per 10 000 patient discharges rose from 7.1 in 1981 to 14.1 in 1984 at a university hospital in the USA [20]. A widespread study between 1997 and 2001, including data from Asia-Pacific, Europe and America, showed that S. maltophilia was the third most frequently isolated non-fermentative bacterium, following P. aeruginosa and Acinetobacter, with a rate of isolation from clinical specimens of 8% [21].…”
Section: Discussionmentioning
confidence: 99%